2015
DOI: 10.1128/aem.04175-14
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Caused by Bath Exposure of Zebrafish (Danio rerio) Larvae to Nervous Necrosis Virus Is Limited to the Fourth Day Postfertilization

Abstract: cNervous necrosis virus (NNV) is a member of the Betanodavirus genus that causes fatal diseases in over 40 species of fish worldwide. Mortality among NNV-infected fish larvae is almost 100%. In order to elucidate the mechanisms responsible for the susceptibility of fish larvae to NNV, we exposed zebrafish larvae to NNV by bath immersion at 2, 4, 6, and 8 days postfertilization (dpf). Here, we demonstrate that developing zebrafish embryos are resistant to NNV at 2 dpf due to the protection afforded by the egg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…( 23 ) were able to reproduce NNV infection in both adult zebrafish and larvae, and relevant mortalities were observed in larvae microinjected with the virus, which was subsequently confirmed by Morick et al. ( 24 ) after bath exposure. The susceptibility of zebrafish larvae to NNV creates an opportunity to easily screen anti-NNV compounds in an in vivo model, as was performed with the antiviral drug ribavirin ( 41 ).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…( 23 ) were able to reproduce NNV infection in both adult zebrafish and larvae, and relevant mortalities were observed in larvae microinjected with the virus, which was subsequently confirmed by Morick et al. ( 24 ) after bath exposure. The susceptibility of zebrafish larvae to NNV creates an opportunity to easily screen anti-NNV compounds in an in vivo model, as was performed with the antiviral drug ribavirin ( 41 ).…”
Section: Introductionsupporting
confidence: 53%
“…Although no viruses, with some exceptions, are typically known to naturally infect zebrafish and cause massive mortality episodes ( 9 , 10 ), several viruses (including those infecting humans) have been studied using zebrafish as a model of infection. In the case of fish, the main diseases caused by viruses have been reproduced in zebrafish: rhabdoviruses such as spring viremia of carp virus (SVCV) ( 11 – 15 ), snakehead rhabdovirus (SHRV) ( 16 ), viral haemorrhagic septicemia virus (VHSV) ( 17 ), and infectious haematopoietic necrosis virus (IHNV) ( 7 ); birnaviruses such as infectious pancreatic necrosis virus (IPNV) ( 18 , 19 ); iridoviruses such as infectious spleen and kidney necrosis virus (ISKNV) ( 20 , 21 ) or European sheatfish virus (ESV) ( 22 ); and nodaviruses such as nervous necrosis virus (NNV) ( 23 , 24 ). Interestingly, two publications reported that zebrafish can be naturally infected by different nodaviruses ( 25 , 26 ); this can probably occur as a consequence of increases in temperature and crowding ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Morick et al . ) and other ornamental species (Furusawa et al . ), and anadromous species, such as Atlantic salmon, Salmo salar (Korsnes et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have highlighted the ability of betanodavirus to induce clinical signs and mortality in experimentally infected freshwater species, for example zebrafish, Danio rerio (Lu et al 2008;Morick et al 2015) and other ornamental species (Furusawa et al 2007), and anadromous species, such as Atlantic salmon, Salmo salar (Korsnes et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of individuals exposed to the bacterial suspension in PVF was significantly higher than those exposed to the suspension of bacteria in PBS (positive control) and presented no significant difference with zebrafish embryos not exposed to the pathogen (negative control). A previous report [ 33 ] has suggested a possible function of PVF against viral infection. In that case, viral infection was tested by bathing 2 dpf embryos without their chorions, or with their chorions pierced, with virus.…”
Section: Resultsmentioning
confidence: 99%